Polski, czeski i słowacki teatr lalek — przenikanie wpływów - Tomaszewska, Ewa (Studia Etnologiczne i Antropologiczne, 2014)
The subject matter is analyzation of the phenomenon of mutual influences between the Czech, Slovak and Polish puppet theatre. This theme is inspired by the significant presence of Czech and Slovak artists on Polish puppet stage. Czech and Slovak puppet theatre have a long and rich tradition. Contrary, Polish puppet theatre has been created freely after the Second World War, without the burden of tradition what became inspiring for Czech and Slovak neighbours. The questions are: is this phenomena conditioned by opening of the borders between the countries, common cultural references to Europe, declining condition of Polish theatre, or is it a result of a constant cultural fluctuation?